Effects of water, salt, and mixing on the rheological properties of bread dough at large and small deformations: A review. Issue 4 (16th May 2022) - Sun, Xinyang; Koksel, Filiz; Scanlon, Martin G.; Nickerson, Michael T.
Abstract: Background and Objective: A direct relationship between dough rheology and bread quality has been clearly revealed to show remarkable significance of studying dough rheological properties throughout breadmaking processes. This review paper has presented the effects of basic ingredients and mixing conditions on dough rheological properties at large and small deformations. Findings: At both large and small deformations, dough rheological parameters have indicated that the variation in dough strength is due to a manipulation of ingredients and mixing conditions. The rheological properties of doughs over a wide range of formulations and processing conditions have been well characterized using the basic rheological models varying in the degree of complexity. Particularly, a power‐law gel model with only two parameters has a good ability for describing the strength and linear viscoelastic behavior of dough. Conclusions: To devise strategies for achieving a desirable product quality, a deep understanding of the effects of ingredients and mixing conditions on dough rheology is in great need. Significance and Novelty: Dough rheology insights not only benefit the bakery industry by screening suitable wheat flours for breadmaking, but also provide knowledge of how to improve dough handling properties during bakery manufacturing.